PERBEDAAN PERILAKU MANAJEMEN LABA AKRUAL DAN RIIL: ANALISIS BERDASARKAN TAHAPAN SIKLUS HIDUP DAN UKURAN PERUSAHAAN - Prasetio, Yudi Wiranata; Lasdi, Lodovicus; Tedjasuksmana, Budianto (Jurnal Akuntansi Kontemporer, 2016)
The objective of this study was to examine whether there are differences in accrual earnings management behavior and real based on life cycle stages and the size of the company. Real earnings management in this study is divided into three proxies are abnormal cash flow operation, abnormal discretionary expenses, and abnormal production costs, while the accrual earnings management is indicated with discretionary accruals. In this study the life cycle of the company are grouped according to the method of Anthony and Ramesh (1992), namely growth, mature, and stagnant, while the size of the companies grouped into three categories, namely too small, medium, and large. The sample in this study is manufacturing companies listed in Indonesia Stock Exchange (IDX) during the period 2006-2013. Find were the techniques used is purposive sampling which produces a sample of 105 companies. Statistical tool used to test the hypothesis in this study is different test parametric Paired Sample T-Test for normally distributed data and non-parametric test different Wilcoxon Signed Rank Test for distributed data is not normal. The results of this study indicate that the company is at the stage of growth and stagnant more likely to perform accrual earnings management, while at the mature stage companies tend to perform real earnings management. In addition, companies are small and medium tend to accrual earnings management, while large-sized companies tend to perform real earnings management.